A construção de sentidos na moda brasileira : a customização do vestuário como espaço de contestação e remodelação do indivíduo nas décadas de 1960 e 1970 - Lago, Cícera Ângela Raymundi (2008)
Fashion is the product of the binomial space-time. Thus, every time and every place, it takes many shapes and colors, printing different meanings: their language, their signs and their expressions. Like that, the central scientific problem is set: were there, in 20 years time, between 1960 and 1979 with domestic and foreign influences, in Brazil, any expressions, or any forms of expression through the body and clothing which used the personalization (or customization) as a sign of clothing and fashion as a language? To solve this problem, this research has as a main goal to understand the personalization of clothing as an area of dispute and remodeling of the individual in the 1960s and 1970s, building a sense of Brazilian fashion from that time. Having the main idea to reach this goal, from the fashion field there is construction of meaning - considering that through it, it is possible to reflect, translate and change the perception of the world and the body, and through the art fashion is made and vice versa: the body becomes the ideal canvas for self-expression of the human being and can be remodeled, manipulated and managed. After that, with the direction of fashion in Brazil, and external determinant influences - the great fashion designers, the cultural context, the influence and power of media, the culture of mass, the essential work of the designer Dener in the specified in decades. The vision of fashion is followed as an area of contestation- the anti-fashion, the counterculture of the hippie movement, the time of release of women and against the dictatorship, expressed by seamstress Zuzu Angel. Finally, since the customization and remodeling of the individual as a reinvention of his or her subjectivity, especially from the years 1960 to 1979. Considering all these aspects, it is concluded that the fashion, driven by the human understanding that creates it, is a form of a language and its range of signs, after chosen and combined by the people, transmits the understood information, because we have already known the meanings of the used pieces. However, the study also concludes that when there is change in signs, such as personalization and customization through the remodeling of the individual, the transmitted message requires a conceptual relocation of people: it happened with the Brazilian fashion of the 1960s and 1970s, which broke the expressive patterns of that period for personalization, creating a new sense of fashion and thereby bringing changes to the entire Brazilian society